Physiologically Relevant Free Ca2+ Ion Concentrations Regulate STRA6-Calmodulin Complex Formation via the BP2 Region of STRA6. Issue 22 (5th November 2021) - Young, Brianna D.; Varney, Kristen M.; Wilder, Paul T.; Costabile, Brianna K.; Pozharski, Edwin; Cook, Mary E.; Godoy-Ruiz, Raquel; Clarke, Oliver B.; Mancia, Filippo; Weber, David J.
Graphical abstract: Highlights: Ca 2+ -bound Calmodulin (CaM) interacts with the BP2 helix of STRA6. CaM exhibits distinct Ca 2+ -dependent and independent interactions with BP2 peptide. The CaM C-lobe interacts with STRA6 BP2 at Ca 2+ concentrations ∼100 nM. As free Ca 2+ increases to 1000 nM, BP2 interacts with the N- and C-lobes of CaM. Ca 2+ signaling regulates vitamin A transport via structural changes in CaM-STRA6. Abstract: The interaction of calmodulin (CaM) with the receptor for retinol uptake, STRA6, involves an α-helix termed BP2 that is located on the intracellular side of this homodimeric transporter (Chen et al ., 2016 [1]). In the absence of Ca 2+, NMR data showed that a peptide derived from BP2 bound to the C-terminal lobe (C-lobe) of Mg 2+ -bound CaM ( Mg CaM). Upon titration of Ca 2+ into Mg CaM-BP2, NMR chemical shift perturbations (CSPs) were observed for residues in the C-lobe, including those in the EF-hand Ca 2+ -binding domains, EF3 and EF4 ( Ca KD = 60 ± 7 nM). As higher concentrations of free Ca 2+ were achieved, CSPs occurred for residues in the N-terminal lobe (N-lobe) including those in EF1 and EF2 ( Ca KD = 1000 ± 160 nM). Thermodynamic and kinetic Ca 2+ binding studies showed that BP2 addition increased the Ca 2+ -binding affinity of CaM and slowed its Ca 2+ dissociation rates (koff ) in both the C- and N-lobe EF-hand domains, respectively. These data are consistent with BP2 binding to the C-lobe of CaM at low free Ca 2+ concentrations (<100 nM) like those found at resting intracellular levels. As free Ca 2+ levels approach 1000 nM, which is typical inside a cell upon an intracellular Ca 2+ -signaling event, BP2 is shown here to interact with both the N- and C-lobes of Ca 2+ -loaded CaM ( Ca CaM-BP2). Because this structural rearrangement observed for the Ca CaM-BP2 complex occurs as intracellular free Ca 2+ concentrations approach those typical of a Ca 2+ -signaling event ( Ca KD = 1000 ± 160 nM), this conformational change could be relevant to vitamin A transport by full-length Ca CaM-STRA6.